Communication and media ethics - Plaisance, Patrick Lee (Handbooks of communication science ;, 2018)
"Ethics in communication and media has arguably reached a pivotal stage of maturity in the last decade, moving from disparate lines of inquiry to a theory-driven, interdisciplinary field presenting normative frameworks and philosophical explications for communicative practices. The intent of this volume is to present this maturation, to reflect the vibrant state of ethics theorizing and to illuminate promising pathways for future research"--